12th International Scientific Conference of Sport Kinetics 2011 CONFERENCE PROGRAMME AND ABSTRACTS (Eigenverlag, 2011)
Zusammenfassungen zu folgenden Themen Abalasei Beatrice, Ungurean Bogdan, Cojocariu Adrian: PUBLIC TYPES OF SPORTS EVENTS IN ROMANIA Gerasevich Anatoly, Yuri Schenovsky, Leo Shitov: SEX DIFFERENCES IN MORPHOLOGICAL PARAMETERS OF THE BODY OF STUDENTS OF SPECIALIZED FACULTY Timoshenkov V. V., Timoshenkova A. N., Borisov V. Y., Starosta V.: ANALYSIS OF FACTORS WHICH INFLUENCE THE VITAL FUNCTIONS OF BELARUSIAN AND POLISH STUDENTS Couto Bruno Pena, Sara Andrade Rodrigues, Rafael Soncin Ribeiro, Marcos Daniel Motta Drummond, Barbara Marcelina Ribeiro Rocha, Leszek Antoni Szmuchrowski: EFFECT OF STRENGTH TRAINING WITH VIBRATION ON BILATERAL FORCE AND IMPULSE DIFFERENCE Balakova Veronika: THE USAGE OF VIDEO INTERACTION GUIDANCE METHOD IN SPORT Bunc Vaclav, Marie Skalska: EFFECT OF WALKING ON BODY COMPOSITION AND AEROBIC FITNESS IN NONTRAINED MEN OF MIDDLE AGE Cepicka Ladislav, Irena Holeckova, Pavel Mautner, Roman Moucek: THE DIFFERENCES IN BRAIN RESPONSE ACCORDING TO THE LEVEL OF MOTOR DEVELOPMENT IN CHILDREN Koptikova Jana, Mikulas Splitek, Lukas Matejovic, Ladislav Cepicka: THE SCORING IN THE TEST OF GROSS MOTOR DEVELOPMENT_2 AND MOVEMENT ASSESSMENT BATTHERY FOR CHILDREN ACCORDING TO LEVEL OF MOTOR DEVELOPMENT Kova. Karel, Marek Waic: SOCIAL SCIENCES OF PHYSICAL EDUCATION AND SPORT IN THE CZECH REPUBLIC. THE TRADITION, HERITAGE OF COMMUNISM, PRESENT TIME AND PERSPECTIVES OF EVOLUTION Kovarova Lenka, Karel Kovar: COMPARISON OF HEART RATE AND THE LACTATE LEVEL OF INDIVIDUAL ANAEROBIC THRESHOLD IN SWIMMING, CYCLING AND RUNNING IN THE TRIATHLON Psalman Vladimir, Martin Zvonar, Ji.i Zhanel, Igor Duvac, Martin Sebera: TIMING IN TENNIS SPORT Fernandez del Valle Maria, Rodriguez-Ruiz David, PhD, Diez Vega Ignacio, Rodriguez-Matoso Dario , Sagastume Fernandez Rafael, Molina Martin Juan, Jose, PhD.: ASOCIATION ANALYSIS BETWEEN BODY COMPOSITION AND SOMATOTYPE CHARACTERISTICS AND ACTN3 GENE IN ELITE SPANISH VOLLEYBALL PLAYERS Rodriguez-Ruiz David, Fernandez-del Valle Maria, Rodriguez-Matos, Dario, Diez Vega Ignacio, Sagastume, Fernandez Rafael, Molina Martin J.J.: FUNCTIONAL DIFFERENCES AMONG KNEE MUSCLES BETWEEN MALE AND FEMALE VOLLEYBALL MIDDLE-BLOCKER Behrooz Imeri, Dilip Kumar Dureha: THE COMPARISON OF BONE MINERAL DENSITY OF LUMBAR SPINES AND FEMORAL BONES BETWEEN MALE ELITE SWIMMERS AND MALE NONATHLETES Asgari Karim, Behnam Ghasemi, Elena Hosepian: THE RELATIONSHIP BETWEEN MASCULINE FEMININE PERSONALITY TYPES AND INTERESTS IN MARTIAL SPORTS Bagherian Mehdi, Vahid Soltani Dehnavi: THE EFFECT OF EIGHT WEEK AEROBIC EXERCISE (BRUCE PROTOCOL) IN THE MORNING AND EVENING ON IMMUNE SYSTEM OF ELITE WRESTLERS Baledi Reza, Farzad Mohammadi, Arash Asefi rad: THE COMPARISON OF OVERALL LEVEL OF SOCIAL DEVELOPMENT IN INDIVIDUAL AND TEAM SPORTS WITH NONE-ATHLETES. Dana Amir, Reza Rezaee Shirazi, Saeed Ghorbani, Faezeh Zamanian: THE EFFECT OF A FEEDBACK TRAINING PERIOD ON LEARNING OF SHOOTING IN INEXPERIENCED SHOOTERS Dana Amir, Reza Rezaee Shirazi, Saeed Ghorbani, Faezeh Zamanian: THE EFFECT OF INSTRUCTION AND MOTIVATIONAL SELF TALK ON PERFORMANCE AND RETENTION OF DISCRETE AND CONTINUOUS MOTOR TASKS Faezeh Zamanian, Elham Forouzandeh, Javid Didari, Mina Haghighi, Azam Hashemi: EFFECTS OF WATER EXERCISE ON FALLING RISK AND POSTURAL CONTROL OF ELDERLY WOMEN WITH KNEE OA Fakhrabadi Gholam Reza Karami, Behnam Ghasemi, Zhaleh Bahramiyan: AN ASSESSMENT OF THE SELECTED CORRECTIVE-BALANCED EXERCISES EFFECT ON THE DYNAMIC BALANCE OF PRIMARY SCHOOL GIRLS WITH FLAT FOOT Fathollahi Shorabe Fazllolah, Sheykh Saraf Bahare, Jalali Dehkordi Khosro, Nouri Reza: EFFECT OF 12 WEEKS SWIMMING TRAINING IN SOME INFLAMMATORY INDEXES (CRP, IL.6) IN 9 TO 11 YEARS GIRLS Foroozandeh Elham: SPATIAL ATTENTION IN BASKETBALLISTS: A NEUROPSYCHOLOGIC STUDY IN SPORT Ghasemi Behnam: THE IMPACT OF CORRECTIVE & THERAPY EXERCISES ON BACK NON-ATHLETIC HYPERLORDOSIS DYSMENORRHEAL WOMEN Ghasemnian Agha Ali, Khosrow Jalali Dehkordi, Abasali Ghaeini, serous chobeineh, Ali Jalali Dehkordi, Fazllolah Fathollahi Shorabe: EFFECT OF AN SPORT DRINK ON ENDURANCE, BLOOD GLUCOSE, HEART RATE AND RPE IN MALE RUNNERS Maleknia Hamid Reza, Fazllolah Fathollahi Shorabe , Khosrow Jalali Dehkordi , Bahare Sheykh Saraf: A COMPARISON OF THE EFFECT OF TWO TYPES OF RESISTANCE, ENDURANCE TRAINING ON GROWTH HORMONE(GH) SECRETION IN AGING MALE Moradi Hemmat Allah, Arsalan Damirchi , Bahman Mirzaii: THE EFFECT OF INTERVAL AND CONTINUOUS TRAINING ON AEROBIC POWER, BODY COMPOSITION AND MOOD STATES Moradi Kelardeh Baharak, Mehdi Namazizadeh, Zohreh Meshkati, Reza Karami: RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND RANKING OF EPEE WEAPON FENCERS IN DIFFERENT LEVELS OF PERFORMANCE Nazerian Iman, Mohammad Reza Iravani, Akram Soltani: STUDY OF EFFECT OF A SELECTED AEROBIC EXERCISE ON SOME ITEMS OF IMPROVING OCCUPATIONAL PERFORMANCE MANAGERS IN MOBARAKEH STEEL COMPLEX Sheykh Saraf Bahare, Fathollahi Shorabe Fazllolah, Nouri Reza, Jalali Dehkordi Khosro: EFFECT OF 12 WEEKS SWIMMING TRAINING IN SOME INFLAMMATORY INDEXES (CRP, IL.6) IN 9 TO 11 YEARS GIRLS Soleimani Athefeh, Behnam Ghasemi, Farzaneh Taghian, Gholamreza Karami Fakhr Abadi :THE EFFECT OF SPORT MASSAGE ON LEUKOCYTES (WBC) AFTER ONE SESSION OF INTENSE EXERCISE IN FEMALE FUTSUL PLAYERS Soltani Akram, Iman Nazerian: REPRESENTING OF A MODEL FOR COMPILING OF COMPETENCES REQUIRED BY MANAGERS OF SPORT FEDERATIONS IN IRAN Soltani Dehnavi Vahid, Mehdi Bagherian: THE COMPARISON OF ONE SESSION AEROBIC EXERCISE (KACH-MAK ARDEL PROTOCOL). IN THE MORNING AND EVENING ON IMMUNE SYSTEM OF ELITE WRETLERS Assarzadeh Nooshabadi M., M. Akbarpoor: THE EFFECT OF AEROBIC EXERCISE ON VASCULAR INFLAMMATORY PARAMETERS IN OBESE MEN Belli G., Tentoni C., Anderson G.: CORE TRAINING FOR BALANCE AND PERFORMANCE Ciairano Silvia, Mattia Roppolo, Massimiliano Gollin, Anna Mulasso, Luca Beratto, Antonio Bertolotto, Alberto Rainoldi: THE ROLE PLAYED BY THE PERCEPTION OF FATIGUE IN THE RELATIONSHIP BETWEEN ADAPTED PHYSICAL ACTIVITY AND QUALITY OF LIFE IN WOMEN WITH MULTIPLE SCLEROSIS Klonova Alina, Leonids Zilinskis, Juris Klonovs, Andrea Giovanardi, Antonio Cicchella: RELATION BETWEEN PHYSIOLOGY AND BIOMECHANICS IN SPORT DANCERS Neiva Henrique P., Filipa M. Pereira, Pedro G. Morouco, Mario C. Marques, Daniel A. Marinho: THE EFFET OF WARM-UP IN 100 M SWIMMING PERFORMANCE Piras Alessandro, Lobietti Roberto, Squatrito Salvatore: REACTION TIME AND OCULAR MOVEMENTS IN VOLLEYBALL Balawejder Katarzyna, Ma.gorzata S.owi.ska-Lisowska, Marek M.dra.: RELATION BETWEEN PHYSICAL ACTIVITY AND SYMPTOMS OF LATE ONSET HYPOGONADISM (ANDROPAUSE) IN MALE POPULATION AGED 45-75. Bibrowicz Karol, Bartosz Bibrowicz: APPLICATION OF DIGITAL INCLINOMETER- DUOMETR FOR SPATIAL LOCATION AND RANGE OF MOTION OF PELVIC GIRDLE Bigosi.ska Monika, Zbigniew Szygu.a: EVALUATION OF HEALTH BEHAVIOUR OF YOUNG WOMEN . STUDENTS OF PWSZ IN NOWY S.CZ . THE PHENOMENON OF SELF-HEALING OR HEALTH MONITORING Bubka Zofia: THE INFLUENCE OF PHYSICAL ACTIVITY ON PSYCHOPHYSICAL EFFICIENCY AND HEALTH IN ELDERLY PEOPLE BETWEEN 55.75 YEARS OLD Buraczewski Tomasz, Leszek Cicirko: THE DIFFERENCES IN THE EFFECTIVENESS OF FOOTBALL GAME BETWEEN THE BEST TEAMS IN XII EUROPEAN CHAMPIONSHIP IN 2008 Cebula Agata, Anna Tyka, Andrzej Markowski, Szczepan Wiecha, Aneta Teleg.ow, Anna Marchewka: THE CHANGES IN THE PHYSIOLOGICAL RESPIRATORY PARAMETERS DURING WINTER SWIMMING IN MEN Cicirko Leszek, Tomasz Buraczewski: THE EFFECT OF FOCUSED TRAINING PROCESS ON THE PROGRESSION OF MOTOR SKILLS AND TECHNICAL ABILITIES OF CHILDREN TRINING FOOTBALL Dancewicz Tomasz, Agnieszka Zabrocka: EFFICIENCY OF SHAPING FLEXIBILITY IN DANCE SPORT ATHLETES AT THE BEGINNING STAGE OF TRAINING Duda Henryk: EVALUATION INTELLECTUALISATION TEACHING MOVEMENT TECHNIQUES IN TERMS OF EFFECTIVE AND HEALTHY FOR TRAINING YOUNG FOOTBALL PLAYERS Dybi.ska Ewa, Katarzyna Kucia-Czyszczo.: RESPIRATORY PARAMETERS IN RELATION´TO THE14 YEARS OLD SWIMMERS SPORT RESULTS Forczek W., Staszkiewicz R.: THE IMPACT OF PREGNANCY ON THE WOMEN´S WAY OF WALKING Fr.czek Barbara, Maria Gacek: FOOD PRODUCTS CONSUMPTION FREQUENCY AMONG ATHLETES COMPARING TO THE RECOMMENDATION OF THE SWISS FOOD PYRAMID Gierat Boguslawa:POSTURAL STABILITY AND RISK OF DYSLEXIA IN 6 YEARS OLD CHILDREN Gierat Boguslawa: THE RELATIONSHIP BETWEEN MOVEMENT COORDINATION AND SCHOOL READINESS IN 6 YEARS OLD CHILDREN G..b Grzegorz, Jerzy Cempla, Marcin Maciejczyk, Aleksandra Gilis-Januszewska, Beata Piwolska: CHANGES IN AEROBIC CAPACITY IN NEWLY DIAGNOSED WOMEN WITH GLUCOSE METABOLISM DISTURBANCES AND WITH SIMPLE OBESITY AFTER 12- WEEK LOW CALORIE DIET AND STANDARDIZED TRAINING PROGRAM G..b Grzegorz, Joanna Ulfi k: INJURY INCIDENCE IN TOP-LEVEL POLISH GYMNASTS WITH REGARD OF CAUSES OF TISSUE DAMAGE IN ATHLETES´ OPINION Grzybek Joanna, Dariusz Mucha, Sebastian Grzybek, Anna Gumulka: EFFECTS OF DANCE TRAINING ON THE PHYSICAL ABILITIES OF INDIVIDUALS WITH MOTOR DISABILITIES Juras Grzegorz, Kajetan S.omka, Mariusz Furmanek, Grzegorz Sobota: RELIABILITY OF THE OPTOJUMP SYSTEM AS A NEW TOOL FOR EVALUATION OF MOTOR COORDINATION Kalina Roman Maciej, Bart.omiej Jan Barczy.ski: THE ABILITY OF THE PRECISE ACTION BEFORE AND DURING A PHYSICAL EFFORT AS INTER-FEATURE Ka.amacka Ewa: MOTOR ACTIVITY . BASIC PRINCIPLES OF HEALTH IN THE PAST AND IN OUR TIMES Kobiela Filip: THE TWO KINDS OF SPORTS & HUMAN MOVEMENT ACTIVITIES Ko.aczkowski Zdzis.aw, Tadeusz Rynkiewicz, W.odzimierz Starosta, Ryszard Kopa.ski: RESEARCH FOR THE MEASUREMENT OBJECTIFICATION OF HUMAN JUMPING ABILITIES Konarski Jan, Robert M. Malina, Ryszard Strzelczyk: RUNNING SPEED OF ELITE FIELD HOCKEY PLAYERS: VARIATION WITH AGE BETWEEN 17 AND 40 YEARS Krystyna Ro.ek, S.awi.ska Teresa, Ignasiak Zofi a, Skrzek Anna, Fugiel Jaros.aw, Pos.uszny Pawel: ASSESSMENT OF RESPIRATORY FUNCTION PARAMETERS DECLARED PHYSICAL ACTIVITY AND PHYSICAL FITNESS IN PEOPLE OLDER Kucia-Czyszczo. Katarzyna, Ewa Dybi.ska: INTERIOR AND EXTERIOR FACTORS SWIMMING EFFICIENCY OBSERVED AMONG LESS - SKILLED SWIMMERS Lyakh Vladimir, Bartosz Rutowicz, Zbigniew Witkowski: GENDER DIFFERENCES IN SPEED AND POWER ABILITIES BETWEEN MALE AND FEMALE SOCCER PLAYERS OF POLISH NATIONAL TEAMS Lyakh Vladimir, Janusz Jaworski, Janusz Brudecki, Przemys.aw Bujas, Dorota Palik, Marek Palik: THE LEVEL OF DEVELOPMENT OF COORDINATION MOTOR ABILITYS OF STUDENTS COLLEGIUM MEDICUM UJ IN THE ASPECT OF SOCIO - ECONOMICAL DIFFERENCES AND THE DECLARED PHYSICAL ACTIVITY Lyakh Vladimir, Przemys.aw Bujas, Dorota Palik, Leszek Gargula, Marek Palik Janusz Brudecki: SEXUAL DIMORPHISM OF COORDINATING MOTOR AREA IN THE CASE OF CM UJ STUDENTS Maku.a Waldemar: WIDELY EDUCATED BRITISH SENIORS´ ATTITUDES ON THE SIGNIFICANCE OF REGULAR PHYSICAL ACTIVITY IN THEIR DAILY LIVING ACTIVITIES CURRICULA My.liwska Katarzyna: BEAUTY CARE . OPPORTUNITY OR THREAT TO PHYSICAL ACTIVITY Niewiadomska Monika, Mariya Radziyevska: USE OF PHYSICAL ACTIVITY FOR CORRECTION OF METABOLIC STATE IN CHILDREN WITH TYPE 1 DIABETES Ni.nikowski Tomasz, Micha. Biegaj.o: THE ANALYSIS OF DOUBLE SALTO BACKWARD TUCKED AND DOUBLE SALTO BACKWARD STRAIGHT PERFORMED BY ELITE ACROBATS Nowak Marcin, Mariusz Ozimek, Robert Rokowski: SELECTED SOMATIC AND BIOMECHANICAL PARAMETERS IN THE SPRINT RACE 100 M MEN Nowak Mariusz, Ryszard Panfi l: SCORING ABILITIES IN THE GAME OF TENNIS (PRAGMATIC STUDY OF UNIQUE CASES) Nowak Mariusz, Ryszard Panfi l: SCORING ABILITIES IN THE GAME OF TENNIS (PRAGMATIC STUDY OF UNIQUE CASES) Olex-Zarychta Dorota, Robert Koprowski, Grzegorz Sobota, Zygmunt Wrobel: EFFECTIVNESS OF SENSORIMOTOR TRAINING IN HEALTHY ADULTS IN DIFFERENT CONDITIONS OF INSTABILITY . A PILOT STUDY Omorczyk Jaros.aw, Leszek Nosiadek, Andrzej Nosiadek: THE BENEFIT OF HIGH-SPEED CAMERA RECORDING DURING BACK HANDSPRING TECHNIQUE A BIOMECHANICAL ANALYSIS Panfi l Ryszard: THE EFFECTIVENESS OF COOPERATION IN THE TEAM GAME (PRAGMATIC STUDY OF UNIQUE CASES) Pilch Wanda, Dorota Gryka-Nowaczyk, Marta Szarek, Zbigniew Szygu.a: EFFECT OF FINNISH SAUNA BATHING ON QUANTITATIVE CHANGES OF WHITE BLOOD CELLS IN TRAINING AND NON-TRAINING MEN Pilch Wanda, Szczepan Wiecha, .ukasz Tota: FINNISH SAUNA AS AN ELEMENT OF BIOLOGICAL RECOVERY IN THE VOLLEYBALL PLAYERS Przybylski Stanis.aw, Piotr Makar,: BASKETBALL TEST AS AN INDICATOR OF DIAGNOSTIC AND CONTROL FITNESS LEVEL Put M.: EVALUATION OF THE INFLUENCE OF NORDIC WALKING ON ERECTOR SPINE MUSCLE BIOELECTRICAL ACTIVITY ASSESSED DURING WALKING IN PATIENTS WITH LOW BACK PAIN Radziyevska Mariya, Pawel Radziyevsky: THE COMPARISON OF EFFICIENCY OF NATURAL AND ARTIFICIAL HYPOXIC TRAINING IN THE ELITE SPORT Radziyevska Mariya, Pawel Radziyevsky, Monika Niewiadomska, Tatyana Dyba, Mikhail Kalinski, Nejele Jasczanienie, Egle Kemerite, Alex Bilkevitz: ANALYSES OF THE PARTICULARITIES OF THE RECOMMENDED PHYSICAL ACTIVITIES FOR OBESE AND OVERWEIGHT CHILDREN 7-9 YEARS OLD IN POLAND, UKRAINE, LITHUANIA, ISRAEL, USA Radziyevsky Pawel, Mariya Radziyevska, Michael Kalinski: THE ROLE OF BLOOD GEMOGLOBIN CONTENT INCREASE IN THE BODY STATE IMPROVEMENT OF HIGH-QUALIFIED FEMALE ATHLETES SPECIALISED IN SPORTS GAMES Ro.ek-Piechura Krystyna, Katarzyna O.dak: EVALUATION OF QUALITY OF LIFE, PHYSICAL FITNESS AND ACTIVITY RESIDENTS OF CARE AND ADAPTATION CENTER IN WROCLAW Rynkiewicz Mateusz: ASYMMETRY OF SPINAL SEGMENTS MOTION IN CANOEISTS AND THE SPORTS RESULTS Rynkiewicz Tadeusz, Mateusz Rynkiewicz, Jacek Biernacki, Piotr Zurek, Henryk Kos, Ma.gorzata Wojcik: COMPOSITION OF THE BODY WEIGHT OF YOUNG CANOEISTS DEPENDING ON AGE, GENDER AND SPORTS SPECIALIZATION Rynkiewicz Tadeusz, Piotr .urek, Mateusz Rynkiewicz, Zdzis.aw Ko.aczkowski, Ewa Ziemann: METHOD OF THE STRENGTH MEASUREMENT OF THE STRIKE AT BALL IN TENNIS Sadowski Jerzy, Andrzej Mastalerz, Tomasz Ni.nikowski: BANDWIDTH FEEDBACK IN LEARNING COMPLEX MOTOR SKILLS Sakowicz-Kostecka Joanna, Bogdan Sakowicz: ANALYSIS OF SPORTS RESULTS IN THE CONTEXT OF WORLD´ AND POLAND´ S TOP TENNIS PLAYERS´ SOMATIC-MOTOR POTENTIAL Seweryniak Tomasz, .ukasz .ukasik, Dariusz Mroczek: EFFICIENT ANALYSIS AND EVALUATION OF DISTINGUISHED TEAM DEFENSIVE ACTIONS IN WOMEN´ BEACH VOLLEYBALL Smrokowska-Reichmann Agnieszka: MOVING-IN-THE-WORLD: THE NEW CATEGORIES OF DYNAMIC BODILINESS IN HERMANN SCHMITZ´ PHILOSOPHY Supernat Katarzyna, Andrzej Sagalara: SUBJECTIVE SLEEP QUALITY AND OFF LINE LEARNING Szeklicki Robert: PHYSICAL FITNESS NORMS IN CHILDREN AND ADOLESCENTS: THE PHYSICAL EDUCATION APPROACH Sztafa Katarzyna, Katarzyna Zwoli.ska-Mirek, Pawe. Ko.uch: OVERWEIGHT AND OBESITY AMONG CHILDREN AND ADOLESCENTS IN NOWY S.CZ COMPARED WITH THE POPULATION OF OTHER POLISH CITIES Tataruch Magdalena, Ewa Sadowska-Kr.pa, Janusz Iskra, Tomasz Klisz: AEROBIC CAPACITY AND PHYSIOLOGICAL, BIOCHEMICAL AND TRAINING PARAMETERS IN AMATEUR ENDURANCE RUNNERS Tulej Konrad, Dobrza.ski Pawe.: PHYSICAL FITNESS TESTS IN PHYSICAL EDUCATION IN SCHOOL PRACTICE W.sik Jacek: INFLUENCE OF DIFFERENT VERSIONS OF THE STRAIGHT FORWARD PUNCH ON THE OBTAINED FORCE, ENERGY AND POWER - MEASUREMENTS OF TAEKWONDO ITF ATHLETES´ PERFORMANCE Wojciechowska-Maszkowska Bo.ena, Dorota Borzucka: STABILITY OF POSTURE IN WOMEN OF VARIOUS AGE Wojciechowska-Maszkowska Bo.ena, Pawe. Janisiow: EFFECT OF FATIGUE ON THE STABILITY POSTURAL COMPETITORS PRACTICING TAEKWONDO Zarzeczny Ryszard, Mieszko Podle.ny, Anna Polak: ANAEROBIC CAPACITY LEVEL OF THE AMATEUR MOUNTAIN BIKERS DURING THE FIRST HALF OF THE COMPETITION SEASON Zarzeczny Ryszard, Mariusz Kuberski, Agnieszka Deska, Dorota Zarzeczna, Katarzyna Rydz: CRITICAL SWIMMING SPEED (CSS) EVALUATION IN 12-YEARS OLD BOYS Zima Joanna, Micha. Kuczy.ski: REACTION TIME TASK IN DUAL TASK METHODOLOGY Zowis.o Maria: BETWEEN KINESIS AND ENERGEIA . PHILOSOPHERS ON HUMAN MOVEMENT Neiva Henrique P., Filipa M. Pereira, Pedro G. Morouco, Mario C. Marques, Daniel A. Marinho: THE EFFECT OF WARM-UP IN 100 M SWIMMING PERFORMANCE Novais Maria L., Daniel A. Marinho, Vishveshwar R. Mantha, Rui J. Ramos, Abel I. Rouboa, J. Paulo Vilas-Boas, Antonio J. Silva: THE EFFECT OF DEPTH ON DRAG DURING THE STREAMLINED GLIDE: A THREEDIMENSIONAL CFD ANALYSIS Peixoto Cesar: UNDERSTANDING CRITICAL INFORMATION, BEFORE AND DURING A PLATFORM JUMP: RELATIONSHIP BETWEEN DIAGNOSIS COMPETENCE AND PRESCRIPTION DURING TEACHING PROCESSES Petrica Joao: THE ATTENTION OF YOUNG STUDENTS IN THE PHYSICAL EDUCATION CLASS Rui Paulo, Joao Petrica, Julio Martins: EFFECTS OF EXTRACURRICULAR PHYSICAL ACTIVITY AND SPORT, IN PHYSICAL FITNESS, IN BODY COMPOSITION AND PHYSIOLOGICAL PARAMETERS, THE STUDENTS OF SECONDARY EDUCATION OF THE MUNICIPALITY OF CASTELO BRANCO Andreeva A.M.: TYPE-SPECIFIC FEATURES OF MOVEMENT COORDINATION OF PRIMARY SCHOOL CHILDREN Balsevich V.K.: ENVIRONMENTALLY FRIENDLY APPROACH TO LONG-TERM SPORTS TRAINING Gutnik B., Skurvidas A., Mitzkievichiene D., Cesnavichiene V., Archangelskaja J. Eskina E., Nash D.: GOAL DIRECTED MOVEMENT AND FITTS´ PARADIGM ON A MODEL OF FAST REACHING TASK Krivolapchuk I. A.: AEROBIC AND ANAEROBIC WORKING CAPACITY IN 13- TO 14.YEARS-OLD BOYS DEPENDING ON THE RATE OF PUBERTY Krivolapchuk I. A.: THE FACTOR ANALYSIS AND COMPLEX ASSESSMENT OF PHYSICAL WORKING CAPACITY OF SIX-YEAR-OLD CHILDREN Landa B.H.: MONITORING AND EVALUATION OF STUDENT HEALTH AND PHYSICAL ACTIVITY: METHODS, TECHNIQUES AND TOOLS Lisovskiy Andrey, Prof. Dr. of Habil, Master Tech, Nina Lisovskaya: AUTOMATI"R CONTROL OF SENSOMOTORICS INDEXES IN TRANING PROCESS OF YOUNG ALPINE SKIERS Lisovskiy "@., Lisovskaya N., Mast. Habil: SENSOMOTOR MONITORING OF YOUNG ALPINE SKIERS Lubysheva L.I.: SPORTS CULTURE IN RUSSIAN EDUCATIONAL ENVIRONMENT Malkin V., L. Rogaleva: SETS OF COACHES AND SPORT RESULTS OF YOUNG SPORTSMAN Rogaleva L., V. Malkin: THE SYSTEM OF PSYCHOLOGICAL SUPPORT IN YOUTH SPORT Shakhanova A.V., Lyausheva S.A.: INFLUENCE OF TRAINING LOADS ON ONTOGENETIC DEVELOPMENT AND REGULATOR- ADAPTIVE POTENTIALITIES OF YOUNG FOOTBALL PLAYERS Sonkin Valentin, Ritta Tambovtseva, Galina Maslova, Diana Bukreeva, Rimma Vasilieva, and Vladim i rDemin: AGE DEVELOPMENT OF MUSCULAR FUNCTION ENERGY SUPPLY Nichifor Florin, Dumitru Iulian: CULTURAL SPECIFICITY WITHIN A SPORTS ORGANISATION (SPORTS CAMP) Popescu Veronica: COMPARATIVE ANALYSIS OF THE FAIR-PLAY VARIABLES, SELF-DETERMINATION AND SOCIAL INTEGRATION ATHLETS Ungurean Bogdan, Cojocariu Adrian, Abalasei Beatrice: CARDIO-RESPIRATORY FUNCTION IN CHILDREN WITH MENTAL DISABILITY AND CHILDREN WITH DOWN SYNDROME Jevtic Branislav, Milos Djordjevic: RESIDUALS OF SWIMMING AND ABILITIES IN WATER AND ON LAND Cepkova Alena: PHYSICAL FITNESS AND MENTAL HEALTH OF STUDENTS OF UNIVERSITY Kokinda Marek, Milan Turek, Robert Kandra.: CONSTRUCTION OF THE FACTOR MODEL FOR THE FITNESS ASSESSMENT IN ICE HOCKEY PLAYERS Uva.ek Marian: EVALUATION OF GAMES PERFORMANCE IN BEACH VOLLEYBALL DEPENDENCY LEVELS ATTACK FROM LEVEL OF QUALITY RECORDINGS Zemkova Erika, Olle Gabor, Hamar Du.an: ENHANCEMENT OF POWER IN CONCENTRIC PHASE OF CLOSED CHAIN EXERCISES WITH DIFFERENT COORDINATION DEMANDS Vodicar Janez, Bojan Jost: THE FACTOR STRUCTURE OF THE VARIABLES OF THE LENGTH OF THE JUMPS AND CHOSEN MORPHOLOGICAL CHARACTERISTICS OF SKI JUMPERS AND THEIR EQUIPMENT Karli U., Acikada C., Hazir T.: VALIDATION OF FOOT TO FOOT BIOELECTRICAL IMPEDANCE ANALYSIS TO HYDROSTATIC WEIGHING IN ELITE MALE WRESTLERS Chermit K.D.: SPORTS LATERAL STRESS (PROBLEM STATEMENT) Chernyak A.N., Lyakh U.E., Zenin O.K.: QUATTITATIVE EVALUTION OF PSYCHOPHYSIOLOGICAL CONDITION OF A PERSON Sokrut Valery, Igor Shvirenko, Elena Povazhnaya, Vadim Popov: REHABILITATIVE APPROACH IN A SPORTS MEDICINE Sokrut Valery, Igor Shvirenko, Elena Povazhnaya, Inna Zubenko: THE REHABILITATION PROGRAM .LONGEVITY. Sokrut Valery, Igor Shvirenko, Elena Povazhnaya, Inna Zubenko, Irina Tereschenko: THE REHABILITATION PROGRAM .VEGETATIVE PASSPORT Jo.t Bojan, Janez Vodi.ar: CORRELATION BETWEEN LENGTH OF THE JUMPS AND CHOSEN KINEMATIC VARIABLES AT THE EARLY FLIGHT POSITION IN SKI JUMPING ANNEKS Anna Pozna.ska, Zuzanna Filar, Katarzyna Filar-Mierzwa: THE ROLE OF EURHYTHMICS AND DANCE CLASSES IN INFLUENCING THE PHYSICAL AND MUSICAL DEVELOPMENT OF YOUNG SCHOOLCHILDREN Jozef Bergier, Ph.D. Barbara Bergier, Ph.D. Zofi a Kubinska: LEISURE TIME AND NURSES´ PHYSICAL ACTIVITY Pawe. Ci.szczyk, Agnieszka Maciejewska, Marek Sawczuk: ASSOCIATION OF THE AMPD1 T34C POLYMORPHISM IN POLISH POWER-ORIENTED ATHLETES Henryk Duda: ASSESSMENT OF GROUP ACTIVITIES IN THE GAME FOOTBALL PLAYERS (FOR EXAMPLE, MATCH POLAND: GERMANY IN THE EURO 2008 TOURNAMENT) Dybek Tomasz, Szygu.a Renata, Klimek Andrzej, Tubek S.awomir: THE AEROBIC AND ANAEROBIC CAPACITY AND SELECTED BLOOD COUNT PARAMETERS AFTER 10 SESSIONS OF WHOLE BODY CRYOSTIMULATION Iosif M. Feigenberg, Wac.aw Petry.ski: PROBABILISTIC PROGNOSIS IN SPORT KINETICS Joanna Grzybek, Dariusz Mucha, Sebastian Grzybek, Anna Gumu.ka: WHEELCHAIR BALLROOM DANCING A SIGNIFICANT FORM OF REHABILITATION WITHIN THE SCOPE OF PSYCHOPHYSICAL HOMEOSTASIS Branislav Jevtic: SCIENTIFIC SYSTEM IN OLYMPIC PROGRAMME MANAGEMENT A. Karpi.ska, K. Podciechowska, W. Starosta: COMPARISON OF THE LEVEL OF GLOBAL MOVEMENT COORDINATION, SPACETIME ORIENTATION AND JUMPING ABILITIES OF PEOPLE WITH DIFFERENT TYPES OF FUNCTIONAL ASYMMETRY . A PILOT STUDY Vladimir Korenberg: ANALYSIS OF HUMAN MOTORICITY . A KINESIOLOGICAL APPROACH Szymon Krasicki, Janusz Brudecki, Magdalena Wojciak: SPORTS ASPECTS OF HIGH MOUNTAIN SKIING I. A. Krivolapchuk: THE FACTOR ANALYSIS AND COMPLEX ASSESSMENT OF PHYSICAL WORKING CAPACITY OF SIX-YEAR-OLD CHILDREN Hugo Louro, Ana Conceicao, Marco Branco, Vitor Milheiro, Marta Martins, Aldo Costa: KINEMATIC ANALYSIS OF THE LOWER LIMB WHILE PERFORMING A SQUAT AT A STEP PLATFORM . EXPERT AND NON EXPERT COMPARISON Marcin Maciejczyk, Jadwiga Szymura, Magdalena Wi.cek , Joanna Gradek, Jerzy Cempla: THE CHANGES OF PHYSIOLOGICAL COST OF RUNNING DURING PUBERTY IN OVERFAT BOYS Hamid Reza Maleknia, Fazllolah Fathollahi Shorabe, Khosrow Jalali Dehkordi, Bahare Sheykh Saraf: A COMPARISON OF THE EFFECT OF TWO TYPES OF RESISTANCE,ENDURANCE TRAINING ON GROWTH HORMONE(GH) SECRETION IN AGING MALE Rogaleva L, Malkin V., Teriaeva M.: THE SYSTEM OF PSYCHOLOGICAL SUPPORT IN YOUTH SPORT Mansooreh Arefi nia Behnam Ghasemi: ASSESSMENT OF INCIDENCE OF INJURY IN ELITE KARATE PLAYERS DURING A SEASON OF RACING Maria Alicja Nowak, Leonard Nowak: REALIZATION OF HEALTHY LIFESTYLE BY WOMEN UNDERTAKING PHYSICAL ACTIVITY Iman Nazerian, Alireza Zamani: THE COMPARISON OF COMPETITIVE TRAIT ANXIETY, COMPETITIVE STATE ANXIETY, AND SELF-CONFIDENCE AMONG MALE ATHLETES OF CONTACT SPORTS AND IN-CONTACT SPORTS Pa.ka Tomasz, Lech Grzegorz, Tyka Anna, Stawiarska Aleksandra, Cebula Agata, Tyka Aleksander, Krawczyk Robert: THE DIFFERENCES IN AEROBIC AND ANAEROBIC PERFORMANCE LEVEL OF JUDO ATHLETES AT VARIOUS AGE GROUPS Rivilla-Garcia, J., Lorenzo J., Sampedro J.: DIFFERENCES IN THE JUMP CAPACITY DEPENDING ON THE DEGREE OF OPPOSITION IN THE HANDBALL JUMP THROW A. Tambovsky: SPORTS OPHTHALMOERGONOMICS AND ITS SOME POSSIBILITIES Alireza Zamani, Iman Nazerian: THE COMPARISON OF TRAIT ANXIETY, STATE ANXIETY, AND SELF-CONFIDENCE AMONG MALE ATHLETES OF TEAM SPORTS AND INDIVIDUAL SPORTS IN THE COUNTRY Monika Bigosi.ska, Zbigniew Szygu.a: EVALUATION OF HEALTH BEHAVIOUR OF YOUNG WOMEN . STUDENTS OF PWSZ IN NOWY S.CZ . THE PHENOMENON OF SELF-HEALING OR HEALTH MONITORING Monika Bigosi.ska, Zbigniew Szygu.a: EVALUATION OF HEALTH BEHAVIOUR OF YOUNG WOMEN . STUDENTS OF PWSZ IN NOWY S.CZ . NUTRITION AND PHYSICAL ACTIVITY